Antibacterial activity of Stichopus hermanii and Stichopus variegatus methanol extract - Susanto, Hendra; Safithri, Mega; Tarman, Kustiariyah (IPB University, 2018)
Since 500 years ago sea cucumber has been used as wound healing medicine. Sea cucumbers are thought to function as a cell growth factor and have the potential as an antibacterial agent. This study aims to determine whether the methanol extract of sea cucumber has antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa so that it can be used to help diabetic wound healing of people infected with the same bacteria. The extraction method used was maceration with methanol to dried frozen simplicia. The simplicia was obtained by freeze drying to liquid preparation of heated fresh sea cucumber. The antibacterial activity test was performed using well diffusion method. There were no any antibacterial activity found in the two methanol extracts of sea cucumber. Keywords: antibacterial agent, Stichopus hermanii, Stichopus variegatus